Sosialisasi Hukum Agraria (Pertanahan) Kepada Masyarakat Dusun Giyasan dan Kawungon Desa Bumirejo Kecamatan Mungkid - Afin Prianda; Galih Putra Pamungkas; Farikhatul Hidayah; Ajeng Sholikhawati; Intan Amalia Putri; Silva Ayu Karimah; Faila Al Faina; Dwi Mei Laila Nurul Baiti; Tarisa Dinar Alifia (Universitas 45 Surabaya, 2024)
Agrarian law is a set of regulations, one of which regulates land registration. Land registration is important to be socialized, the socialization carried out at the Bumirejo Village Hall aims to enable the people of Bumirejo Village to increase their knowledge of the importance of land legality. After observing that there are still many people in Bumirejo Village who do not understand land matters so that quite a few residents experience cases of land disputes, it is very important to carry out socialization of agrarian law. So that through this socialization, parties experiencing land disputes can gain legal certainty and a sense of justice in resolving the problems they are facing. Then this socialization was carried out face-to-face by bringing in speakers from Tidar University Law Lecturers who discussed the legality of land, how to resolve land disputes, and the stages of submitting land disputes. The results of the socialization made the people of Bumirejo Village understand the importance of awareness of land law which can be used to socialize and become citizens who always obey the regulations in force in Indonesia.